2020
DOI: 10.3390/pathogens9020145
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of Two Cucumber Cultivars with Different Sensitivity to Cucumber Mosaic Virus Infection

Abstract: Cucumber mosaic virus (CMV), with extremely broad host range including both monocots and dicots around the world, belongs to most important viral crop threats. Either natural or genetically constructed sources of resistance are being intensively investigated; for this purpose, exhaustive knowledge of molecular virus-host interaction during compatible and incompatible infection is required. New technologies and computer-based “omics” on various levels contribute markedly to this topic. In this work, two cucumbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 108 publications
(111 reference statements)
2
5
0
Order By: Relevance
“…Components of the banana protein biosynthesis system such as 40S ribosomal protein SA, rRNA biogenesis protein/40S assembly factor RRP5, glutamine- and glycine-tRNA ligases, elongation factor 1α, and 60S processome rRNA methyltransferase were all observed to be recruited by the invading pathogen to promote the biosynthesis of its own proteins for successful subversion of the host’s cells. Similar findings were obtained in a previous comparative transcriptomics study following cucumber mosaic virus (CMV) infection in the susceptible cucumber genotype, ‘Vanda’, where structural components of the ribosome and the translation biological process were substantially enriched and up-regulated 84 .…”
Section: Discussionsupporting
confidence: 85%
“…Components of the banana protein biosynthesis system such as 40S ribosomal protein SA, rRNA biogenesis protein/40S assembly factor RRP5, glutamine- and glycine-tRNA ligases, elongation factor 1α, and 60S processome rRNA methyltransferase were all observed to be recruited by the invading pathogen to promote the biosynthesis of its own proteins for successful subversion of the host’s cells. Similar findings were obtained in a previous comparative transcriptomics study following cucumber mosaic virus (CMV) infection in the susceptible cucumber genotype, ‘Vanda’, where structural components of the ribosome and the translation biological process were substantially enriched and up-regulated 84 .…”
Section: Discussionsupporting
confidence: 85%
“…Recent advancements in virus research increasingly reveal good relevance of transcriptome data for cell and organism performance (120)(121)(122)(123). It is also understood that it will be important to focus on gene sets (Preprint 124).…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 infection was associated to marked increase in intracellular glucose and transcriptional modulation in glucose metabolism along with elevated lactate levels (32). Several authors report that in virus research transcriptome data and a focus on gene sets revealed to be critically relevant for cell and organism performance (43)(44)(45)(46)(47).…”
Section: Background Virus Captures Host Cell Signaling and Metabolismmentioning
confidence: 99%